Individualized parameterization of multiparametric monitors alarms in infarcted patients - Allan Peixoto de Assis; Francimar Tinoco de Oliveira; Flávia Giron Camerini; Roberto Carlos Lyra da Silva; Camila Mendonça de Moraes
ABSTRACT Objective: To measure the magnitude of the effect of an individualized parameterization protocol for hemodynamic alarms in patients with acute myocardial infarction. Method: Pragmatic clinical trial, open label and single arm, whose intervention was performed through a protocol validated and tested in 32 patients using multiparametric monitors. The heart rate, blood pressure, respiratory rate, oxygen saturation and ST segment-monitoring were measured and classified for clinical consistency one hour before and after the intervention, for 64 hours. Results: The protocol obtained Content Validity Index of 0.92. Of the 460 registered alarms, 261 were considered inconsistent before the intervention and 47 after it. The Relative Risk of inconsistent alarms after the protocol was 0.32 (95% CI 0.23-0.43, p <0.0001). Conclusion: The protocol proved to be a protective factor to the appearance of inconsistent clinical alarms of multiparametric monitors.